GROWTH OPPORTUNITY MEMODERASI KINERJA KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS 2021-2024 - Anatasya; Susi Handayani (Media Mahardhika, 2026)
This study investigates the impact of financial performance and dividend policy on firm value, with growth opportunities serving as a moderating variable. The analysis focuses on the non-cyclical consumer goods sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Financial performance is assessed using three primary indicators profitability, liquidity, and leverage while dividend policy is measured by the dividend payout ratio. Employing a quantitative approach, the research draws on secondary data sourced from annual financial reports. The sample was determined via purposive sampling, yielding 216 observations. Data were analyzed through Moderated Regression Analysis (MRA) to evaluate both direct and moderating effects. The findings reveal that profitability and dividend policy exert a positive and significant influence on firm value. In contrast, liquidity demonstrates a significant negative effect, whereas leverage shows no significant impact. Moreover, growth opportunities strengthen the associations between profitability, dividend policy, and firm value, but do not moderate the relationship between liquidity and firm value. Collectively, these results underscore that a firm's profit generating capacity and dividend strategy are pivotal in enhancing firm value.